2018
DOI: 10.1021/acs.inorgchem.8b00027
|View full text |Cite
|
Sign up to set email alerts
|

Multiply Intercalator-Substituted Cu(II) Cyclen Complexes as DNA Condensers and DNA/RNA Synthesis Inhibitors

Abstract: Many drugs that are applied in anticancer therapy such as the anthracycline doxorubicin contain DNA-intercalating 9,10-anthraquinone (AQ) moieties. When Cu(II) cyclen complexes were functionalized with up to three (2-anthraquinonyl)methyl substituents, they efficiently inhibited DNA and RNA synthesis resulting in high cytotoxicity (selective for cancer cells) accompanied by DNA condensation/aggregation phenomena. Molecular modeling suggests an unusual bisintercalation mode with only one base pair between the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 64 publications
0
17
0
Order By: Relevance
“…Interestingly, increasing the incubation time from 0.5 to 2 h had no significant effect on the results (Supplementary Figures S7 and S8), which suggests that the complete disappearance of DNA is caused by a binding event rather than multiple cleavage events. These data collectively suggest that the Co­(III) complexes of ligands 1 – 6 possess significant hydrolytic DNase activity at micromolar concentrations but that the ligand–metal sequestering procedure used successfully for the Cu­(II) complexes (see experimental procedures and Supplementary Figure S2) was unable to remove the Co­(III) complexes from the DNA; presumably this in-turn (i) causes the DNA to be charge neutralized and consequently not to run on the gel or (ii) prevents the ethidium bromide from binding to the DNA. , …”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Interestingly, increasing the incubation time from 0.5 to 2 h had no significant effect on the results (Supplementary Figures S7 and S8), which suggests that the complete disappearance of DNA is caused by a binding event rather than multiple cleavage events. These data collectively suggest that the Co­(III) complexes of ligands 1 – 6 possess significant hydrolytic DNase activity at micromolar concentrations but that the ligand–metal sequestering procedure used successfully for the Cu­(II) complexes (see experimental procedures and Supplementary Figure S2) was unable to remove the Co­(III) complexes from the DNA; presumably this in-turn (i) causes the DNA to be charge neutralized and consequently not to run on the gel or (ii) prevents the ethidium bromide from binding to the DNA. , …”
Section: Resultsmentioning
confidence: 95%
“…These data collectively suggest that the Co(III) complexes of ligands 1−6 possess significant hydrolytic DNase activity at micromolar concentrations but that the ligand−metal sequestering procedure used successfully for the Cu(II) complexes (see experimental procedures and Supplementary Figure S2) was unable to remove the Co(III) complexes from the DNA; presumably this in-turn (i) causes the DNA to be charge neutralized and consequently not to run on the gel or (ii) prevents the ethidium bromide from binding to the DNA. 43,44 Indeed, Schneider 27 et al notes that cleavage experiments with Co(III)-cyclen derivatives required cyanide treatment to sequester the cobalt prior to electrophoresis. Nonetheless, these data do demonstrate very clearly that the Co(III) complexes of the compounds 1−6 bind very strongly to DNA and therefore would not be able to generate a catalytic turnover.…”
mentioning
confidence: 99%
“…The condensation or aggregation phenomena plays a critical role in many antitumor drugs. DNA condensation has become a dynamic useful technique as it can be used to transfer DNA containing genes of therapeutic interest from solution to target cells involving gene therapy [45,46]. Since DNA possess negative charge density due to nucleobases present in the major and minor grooves, positively charged metal ions can easily intercalate within these nucleobases, thus showing molecular recognition and in vivo modification of DNA in the condensed state.…”
Section: Morphological Studiesmentioning
confidence: 99%
“…The cytotoxicity evaluation in cancer cell lines showed an enhanced cytotoxicity compared with the Schiff base ligand; thus, a positive synergetic effect may be occurring [98]. Horman et al developed functionalized Cu(II) cyclen complexes with three (2-anthraquinonyl)methyl substituents that efficiently inhibited DNA and RNA syntheses resulting in high cytotoxicity accompanied by DNA condensation/aggregation phenomena [99]. Sigman et al reported the first set of copper complexes with phen ligand with good cytotoxic activities [100].…”
Section: Coppermentioning
confidence: 99%